Principals' Digital Leadership in Developing a Generative Artificial Intelligence (Gen-AI)-Based Learning Ecosystem in Elementary Schools - Agustin Hanivia Cindy; Nur Rina Priyani Mirsa; Alpendi Alpendi; Achmad Sya’dulla; Kaidah Yunia Wati; Zhou Ruguang; Hamdan Said (Institut Agama Islam Negeri Palopo, 2026)
The integration of Generative Artificial Intelligence (Gen-AI) in the Society 5.0 era has brought significant disruption to the global education landscape. At the elementary school level, institutional leaders often face gaps in official regulations that trigger restrictive rather than enabling policies. This study aims to analyze the role and digital leadership strategies of elementary school principals, identify systemic challenges and emerging supporting factors, and develop a conceptual framework for developing a safe, ethical, and innovative Gen-AI-based learning ecosystem. Using a descriptive qualitative approach with a single case study design, data collection was conducted at BINUS SCHOOL Semarang through triangulation techniques that included in-depth interviews with eight key informants (consisting of the principal, technology coordinator, four class teachers, and two parent representatives), passive participant observation, and analysis of formal school documents. The study results indicate that the digital leadership implemented in this school displays an adaptive profile (Enabling Leadership) through synchronization of the institution's vision, provision of ICT infrastructure based on content filtering, facilitation of digital pedagogical competency training, and regular updates to academic honesty guidelines. Furthermore, interactions within this ecosystem have resulted in the